A happy way to grow old? Grandparent caregiving, quality of life and life satisfaction - Hao Wang; Jan Fidrmuc; Qi Luo (Center for Economic Studies and ifo Institute (CESifo), 2019)
Utilizing the 2015 wave of the China Health and Retirement Longitudinal Study (CHARLS) that covers 7045 households, we study the effect of grandparents looking after grandchildren on quality of life and life satisfaction of grandparents. We find evidence of important favorable effects of grandparents caregiving: when grandparents look after their grandchildren, they are 2.9% less likely to report symptoms of depression, the amount of support that they receive from their children approximately doubles, and are 2.7% (1.1%) more likely to report being very satisfied (completely satisfied). These favorable effects are proportionate to the amount of time spend caring for grandchildren and increase with the number of grandchildren looked after. The favorable effects on mental health seem limited to grandparents living in rural areas and apply especially to grandfathers. The favorable effect on life satisfaction is primarily directly attributable to caring for grandchildren rather than being incurred indirectly due to better health or financial situation of grandparents.
Keywords: D13; O18; 330; grandparenting; quality of life; life satisfaction